Uji Ditribusi Binomial Sebagai Estimasi Probabilitas Kesuksesan Aplikasi Instagram Melalui Kepuasan Pengguna Instagram - Nabila, Nabila Annadhira; Rahmi, Depriwana; Kurniati, Annisah; Yuniati, Suci (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
The purpose of this study is to assess the success rate of the Instagram application using the binomial distribution to calculate the number of successes from n trials in a population of N, where each trial has two possible outcomes: success or failure. The probability of success is p, and the probability of failure is 1-p. The background of the problem of this study is the difficulty of predicting the success of the Instagram application based on user satisfaction, the limitations of statistical analysis methods in predicting application success, the importance of estimating the probability of application success for developing marketing strategies and application development, and the lack of research on the application of the binomial distribution in estimating the probability of success of the Instagram application. This study uses a Likert scale questionnaire to collect data on user experience and satisfaction. This can provide a clearer picture of how well the Instagram application meets user needs and expectations. The research instrument uses a questionnaire to measure user satisfaction. This method is expected to provide important information about things that need to be improved to increase user satisfaction and engagement on the platform.